Spectrum of fungal infections at a tertiary care hospital in Haryana, India - Alim, Alfia; Goel, Nidhi; Chaudhary, Uma (International Journal of Research in Medical Sciences, 2018)
Background: In recent years, fungi have been emerging as a common infection in hospitalised patients of tertiary care centres. The climate of our country is well suited for a wide variety of fungal infections. Within the limited data available, an increased incidence of invasive candidiasis, aspergillosis and other dematiaceous fungi are reported at our tertiary care centre. This study was undertaken to know the prevalence of common fungal infections at a tertiary care hospital in a period of five years. Methods: The various clinical samples received from the patients presenting with clinically suspected fungal infections were subjected to direct microscopy with potassium hydroxide (KOH) and Gram staining. All samples were inoculated in duplicate SDA with or without antibiotics. Results: A total of 8450 suspected fungal etiology samples were received during the five years (2011-2015) included in the study. The most common sample was sputum 2502 (29.6%) followed by skin swabs 2175 (25.7%), urine 1302 (15.4%), blood 875 (10.35%) and BAL 810 (9.5%). Male to female ratio was 5:3. Candida albicans was the predominant isolate followed by non-albicans candida, Aspergillus flavus, Aspergillus fumigatus and dematiaceous fungi. Conclusions: The fungal isolates, which used to be discarded as laboratory contaminants are playing a significant role in pathogenicity of many infections. These organisms are now capable of affecting immunocompromised as well as immunocompetent individuals.